(untitled) (Impetus, 2021)
This article seeks to reflect on the body and how its formability has been given in the postmodern context, a position that is transferred to modern sport, specifically in Rhythmic Gymnastics. This sports practice is enclosed in the paradox of forming the subject from a ductilizing and disciplining look at the same time that it allows a holistic, vindictive and emancipatory vision of it, which allows the recognition of the emotional, in this case, in the Colombian educational context. which presents shortcomings in the incorporation of these topics. It is essential to focus the magnifying glass and give the importance it deserves to sports and emotions, through dynamics such as expression (intrinsic process of Rhythmic Gymnastics) that allows to enhance the different dimensions of the human being, from the cognitive, communicative, creative, affective, which results in a state of well-being, self-knowledge, coexistence in the educational community and in society in general in which the subjects occur.